To release or not to release? Preferences for home equity products in retirement - Karolin Kirschenmann; Caroline Knebel-Seitz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
How do retirees choose among home equity release products? Despite housing wealth being households' largest asset, little is known about preferences for different equity release products. We conduct a survey experiment comparing home annuities, reverse mortgages, and an opt-out option among the German adult population. We find that presentation format (simultaneous vs. sequential) does not affect product choices. The majority of participants prefer no equity release product. Among those selecting equity release, home annuities are preferred over reverse mortgages. Individual characteristics, in particular risk tolerance, bequest motive, and financial literacy predict choices. The latter highlights the importance of consumer education given the complexity of these long-term financial decisions.
Keywords: D14; G20; G51; G53; J26; 330; Equity release products; reverse mortgage; home annuity; retirement planning; financial literacy